Serum from patients with chest pain and significant atherosclerosis resulted in macrophage cholesterol accumulation - Marwan Dawood; Nina Volkova; Dima Namouz; Michael Aviram; Tony Hayek (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2020)
Aims: The aim of our study was to analyze the effect of serum derived from patients with chest pain, with or without significant atherosclerosis, on J774A.1 macrophages cholesterol metabolism. Methods: Thirty-nine patients with chest pain underwent CT Coronary Angiography (CTCA) to assess atherosclerosis. They were divided into three groups (n=13 for each group), according to extent of Coronary Artery Disease (CAD): No disease (NCAD), Non-significant (NSCAD), or significant CAD (SCAD). Results: Serum total cholesterol level was similar in all three groups, whereas the SCAD group had the lowest serum HDL level and highest serum triglyceride levels, compared with the other groups. The patient's serum (30µl) was incubated with J774 macrophages for 18h. Cellular cholesterol mass was found to be significantly higher by 44 percent in SCAD patients compared to NCAD patients, and by 23 percent compared to NSCAD patients.  In parallel, we observed a significant enhanced cholesterol biosynthesis rate by 53 percent in macrophages treated with serum from the SCAD patients, as compared to NCAD patients, or by 17 percent when compared to the NSCAD patients. In accordance with the above results, HMGCR (the rate limiting enzyme in cholesterol biosynthesis) expression was significantly upregulated in macrophages treated with serum from SCAD patients, in comparison to NCAD or NSCAD patients.  Conclusion: These results clearly demonstrate high macrophage atherogenicity for serum harvested from patients with significant atherosclerosis.